Utility of HEARTSMAP-U for psychosocial screening and mental health resource navigation in the young adult population - Shane Murphy; Delnaz Dadkhah Tirani; Jillian Wagg; Karly Stillwell; Liz Lee; Quynh Doan (PLoS ONE, 2026)
Purpose Given the high prevalence of mental health struggles and long wait times for psychological assessment, validated digital self-assessment screening tools can help to address the gap. Our previously validated tool for ages 6–17, MyHEARTSMAP, was adapted to focus on the transition to university. This new tool, HEARTSMAP-U, captures the issues of older youth, addresses student-specific psychosocial needs, and recommends resources matching the type and urgency of their reported needs. Prior to widespread use in the public domain, we aim to validate the psychometric properties of HEARTSMAP-U as compared to a standard mental health intake assessment. Methods We conducted a prospective validation study of students at a Canadian university aged 17–29. Participants completed psychosocial self-assessments using HEARTSMAP-U, which were then directly compared to equivalent, standardized assessments conducted by clinical counselors. We reported the sensitivity and specificity of the participant self-assessments against that of a clinician’s intake evaluation. This considered each respondent’s degree of unmet needs, and through this, each person was provided with a catered list of local supports for each psychosocial domain. Result Of the 619 eligible participants, 536 completed baseline evaluations for analysis. Using HEARTSMAP-U, post-secondary students’ sensitivity of self-identifying any degree of psychiatric concern was 90% (95% CI 83–94%). When clinicians identified no psychiatric concerns, HEARTSMAP-U self-assessments similarly identified either no or mild concern in 70% (95% CI 65–74%) of these participants. Discussion Psychosocial screening with HEARTSMAP-U can be reliably implemented in a post-secondary population as compared to a clinical clinician evaluation. Interestingly, a large cohort of respondents (10%) were deemed to have no psychiatric concerns by clinician evaluation, but severe concerns based on HEARTSMAP-U self-assessment. This specific population may represent a target group for future screening interventions.